Caracterização de resistência de genótipos de soja a Bemisia tabaci biótipo B (hemiptera: aleyrodidae) - Cruz, Patrícia Leite [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Soybean, Glycine max (L.) Merrill, is one of the most important crops in Brazil with high productivity and expressive participation in exports. This leguminous is an important nutritional source for human and their derivatives may be used in animal feed or in the production of renewable energy as biodiesel. Although it has high production potential, the pest attack such as silverleaf whitefly, Bemisia tabaci (Gennadius) biotype B (Hemiptera: Aleyrodidae), undertakes a significant amount of the volume produced. This insect has become pest of economic importance to the soybean crop due to the increasing infestations and difficulties of management. The control of this hemipteran is made mainly through applications of synthetic insecticides, which are often overly utilized, having an impact on human and the environmental health. This situation encourages the study of less aggressive and more efficient alternatives, suitable to the integrated pest management (IPM). In this sense, the use of resistant genotype is considered a valuable tool, which can reduce the population of pests below the economic injury level without socio-environmental damage. In this work, 15 soybean genotypes were evaluated under attack of B. tabaci biotype B to characterize possible types of resistance (antixenosis, antibiosis and tolerance) against this insect. Initially, antixenosis assays were performed (free and no choice). The raise of the colonization of this insect confined to the genotypes and the characteristics of trichomes were also evaluated. In addition, biological performance tests were conducted to characterize the occurrence of antibiosis. In the last step, tolerance tests were conducted ...

A soja, Glycine max (L.) Merrill, é uma das culturas mais importantes para o Brasil, com elevada produtividade e forte participação nas exportações. Essa leguminosa representa uma importante fonte nutricional para o homem e seus derivados podem ser utilizados na nutrição animal ou mesmo na produção de energia renovável, na forma de biodiesel. Embora a cultura apresente elevado potencial, o ataque de pragas, como o da mosca-branca, Bemisia tabaci (Gennadius) biótipo B (Hemiptera: Aleyrodidae), compromete uma parcela significativa do volume produzido. Esse inseto tornou-se praga de importância econômica para a cultura da soja devido às infestações crescentes e dificuldades de manejo. O controle desse hemíptero é feito principalmente através de aplicações de inseticidas sintéticos, os quais são geralmente utilizados de forma abusiva, impactando sobre a saúde do homem e o meio ambiente. Esse quadro estimula o estudo de alternativas menos agressivas e mais eficientes, alinhadas ao manejo integrado de pragas (MIP). Nesse sentido, o uso de cultivares resistentes é considerada uma valiosa ferramenta, podendo reduzir a população das pragas abaixo do nível de dano econômico, sem prejuízos sócioambientais. Neste trabalho, 15 genótipos de soja foram avaliados sob o ataque de B. tabaci biótipo B, visando caracterizar possíveis tipos de resistência (antixenose, antibiose e tolerância) contra o inseto. Inicialmente, foram realizados ensaios de antixenose (com e sem chance de escolha). A evolução da colonização do inseto confinado aos genótipos e a configuração dos tricomas das plantas também foram avaliados. Em adição, foram realizados ensaios de desempenho ...
Characterization of soybean resistance to bemisia tabaci biotype b (hemiptera: aleyrodidae)
Keywords: Soja - Resistência a doenças e pragas; Soja - Melhoramento genético; Mosca branca; Hemiptera; Plantas - Melhoramento genetico; Plant-breeding